DIGITALISASI KEBIJAKAN EKONOMI: STRATEGI ADAPTIF UMKM DALAM EKOSISTEM BISNIS BERBASIS TEKNOLOGI - Mega, Selfia Alke (Journal Education and Government Wiyata, 2025)
The digitalization of economic policies has become a major catalyst in the transformation of micro, small and medium enterprises (MSMEs). Technological advances encourage MSMEs to adapt business strategies that are more flexible, innovative and digitally based. This article discusses how digitalization of economic policies plays a role in supporting MSMEs, the challenges faced, and adaptive strategies that can be implemented. Using qualitative methods based on literature studies, this research found that the success of digitalization of MSMEs is influenced by infrastructure readiness, digital literacy, and technology-oriented policy support. Therefore, synergy between the government, the private sector and MSME players is very necessary to create a competitive business ecosystem in the digital era.